К вопросу об автоматизации вибродиагностики подшипников качения - Чернышенко, А. В.; Павлова, А. А.; Петрушак, В. П. (НТУ "ХПИ", 2007)
Розглянуті питання вібродіагностики дефектів підшипників кочення. Запропоновані загальна спрощена схема пристрою для зняття сигналів вібродатчика та метод подальшої обробки спектрограми, що дозволило з мінімальними витратами, але з чималою вірогідністю проводити вібраційну оцінку підшипників.

The questions of vibration-based diagnostics of frictionless bearings defects are considered. The general simplified scheme of device for the taking down of vibration detector signals and method of further treatment of spectrogram are offered, that allowed to make the vibration estimation of bearings with minimum expenses, but with large enough probability.
Keywords: тихоходные валы; вибрационный сигнал; импульсное возбуждение; свободные колебания; виброанализаторы